Contra-narrativas de la Segunda Guerra Mundial en el cine griego - Mini, Panayiota (Revista de Filología Románica, 2017)
This article examines three Greek films of the mid-1960s which countered the heroic narrative of World War II: Manousakis’s Betrayal, the story of the love affair between a German officer and a Greek Jewish girl; Kyrou’s The Blockade, dramatizing the resistance and the collaboration under the German occupation; and Glykofrydis’s With a Sparkle in the Eyes, depicting a father’s heartbreaking dilemma. The article explicates the war memories that the films proposed, the artistic and ideological filters through which these memories took shape, and the responses of Greek reviewers. Representing World War II in Greek cinema, the article shows, proved a parlous undertaking as filmmakers and critics were simultaneously confronted with national traumas and sensitive political and diplomatic subjects.